Sintesis ZSM-5 dari Fly Ash Sawit Dengan Variasi Waktu Sintesis Dan Waktu Kalsinasi - Rafif Sauqi; Fajril Akbar; Yelmida Yelmida (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Fly ash contains many elements of the high silica used as a source of silica for the synthesis of ZSM-5. ZSM-5 zeolite synthesis is one that is widely used in industry mainly as a catalyst. This is due to the ZSM-5 has a high activity and selectivity in several hydrocarbon conversion reactions. This study aimed to the synthesis of ZSM-5 of fly ash as a silica source without using templates with the time variation of the synthesis and calcination time. Synthesis performed in autoclaf at 190 ° C with a temperature variation of synthesis time 16, 18, 20 and 22 hours, calcination is done in a furnace to a temperature of 500 0 C with a variation of calcination time 4 hours, 5 hours and 6 hours. Synthesis products were analyzed by FTIR. The results showed that the best conditions for the synthesis of ZSM-5 from fly ash oil is at synthesis time of 20 hours and calcination time 4 hours. The content of ZSM-5 produced in the x-ray analysis is as much as 3%.Keyword : Fly ash, ZSM-5, FTIR, and XRD